Angiography and Monitoring of Hemodynamic Signals in the Brain via Optical Coherence Tomography - (:unkn) unknown (My University, 2013)
The brain is a complex network of interconnected neurons with each cell functioning as a nonlinear processing unit. Neural responses to stimulus can be described by activity in neurons. While blood flow changes have been associated with neural activity and are critical to brain function, this neurovascular coupling is not well understood. This work presents a technique for neurovascular interrogation, combining optogenetics and optical coherence tomography. Optogenetics is a recently developed neuromodulation technique to control activity in the brain using light with precise spatial neuronal control and high temporal resolution. Using this method, cells act as light-gated ion channels and respond to photo stimulation by increasing or decreasing activity. Spectral-domain optical coherence tomography (SD-OCT) is a noninvasive imaging modality that has the ability to image millimeter range depth and with micrometer resolution. SD-OCT has been shown to image rodent cortical microvasculature in-vivo and detect hemodynamic changes in blood vessels. Our proposed system combines optogenetics and SD-OCT to image cortical patches of the brain with the capability of simultaneously stimulating the brain. The combination allows investigation of the hemodynamic changes in response to neural stimulation. Our results detected changes in blood vessel diameter and velocity before, during and after optogenetic stimulation and is presented.